INVESTIGATING THE EFFECT OF THE CEO PAY RATIO ON THE FINANCIAL REPORTING QUALITY IN COMPANIES ACCEPTED IN THE TEHRAN STOCK EXCHANGE - Ali Tarkhorani, Peyman Boroumand, Nasim Davoodifar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Financial reporting is one of the sources of information available in capital markets that is expected to play an effective role in developing investment and increasing its efficiency. Improving the quality of financial reporting is a tool to fulfill the responsibility of meeting the needs of society. In this thesis, it has been tried to investigate the effect of the CEO Pay Ratio on the Financial Reporting Quality in companies accepted in the Tehran Stock Exchange. After designing the evaluation indicators of the variables, the information of transactions made in the five-year research period from 2014 to 2018 was collected from the Stock Exchange Organization, the Rahvard Novin software, and the Codal.ir website. The statistical sample consists of 223 companies that have been selected by systematic elimination method, which were totally 1,115 firm-year. This research is a descriptive research in terms of applied purpose and in terms of nature with emphasis on correlation relations. In addition, it falls within the scope of post-event studies. Eviews software has been used to analyze the data and to test the research hypotheses. What can be said in the summary and general conclusion of the research hypotheses test is that the CEO pay ratio has a significant effect on the financial reporting quality. The results obtained in this research are consistent with the documents mentioned in the research theoretical framework and financial literature.